Sex Hormones Regulate Innate Immune Cells and Promote Sex Differences in Respiratory Virus Infection - Kadel, Sapana; Kovats, Susan (Frontiers in Immunology, 2018)
Sex differences in the incidence and severity of respiratory virus infection are widely documented in humans and murine models, and correlate with sex biases in numbers and/or functional responses of innate immune cells in homeostasis and lung infection. Similarly, changes in sex hormone levels upon puberty, pregnancy and menopause/aging are associated with qualitative and quantitative differences in innate immunity. Immune cells express receptors for estrogens (ERα and ER), androgens (AR) and progesterone (PR), and experimental manipulation of sex hormone levels or receptors has revealed that sex hormone receptor activity often underlies sex differences in immune cell numbers and/or functional responses in the respiratory tract. While elegant studies have defined mechanistic roles for sex hormones and receptors in innate immune cells, much remains to be learned about the cellular and molecular mechanisms of action of ER, PR and AR in myeloid cells and innate lymphocytes to promote the initiation and resolution of antiviral immunity in the lung. Here we review the literature on sex differences and sex hormone regulation in innate immune cells in the lung in homeostasis and upon respiratory virus infection.